IL-6 Plasma Levels Correlate With Cerebral Perfusion Deficits and Infarct Sizes in Stroke Patients Without Associated Infections - Hotter, Benjamin; Hoffmann, Sarah; Ulm, Lena; Meisel, Christian; Fiebach, Jochen B.; Meisel, Andreas (Frontiers in Neurology, 2019)
Introduction: We aimed to investigate several blood-based biomarkers related to inflammation, immunity and stress response in a cohort of patients without stroke-associated infections regarding their predictive abilities for functional outcome and explore whether they correlate with MRI markers, such as infarct size or location. Methods: We combined the clinical and radiological data of patients participating in two observational acute stroke cohorts: the PREDICT and 1000Plus studies. The following blood-based biomarkers were measured in these patients: monocytic HLA-DR, IL-6, IL-8, IL-10, LBP, MRproANP, MRproADM, CTproET, Copeptin and PCT). Multiparametric stroke MRI was performed including T2*, DWI, FLAIR, TOF-MRA and perfusion imaging. Standard descriptive sum statistics were used to describe the sample. Associations were analyzed using Fischer’s exact test, independent samples t-test and Spearmans correlation, where appropriate. Results: Demographics and stroke characteristics were as follows: 94 patients without infections, mean age 68 years (SD 10.5), 32.2% of subjects were female, median NIHSS score at admission 3 (IQR 2-5), median mRS three months after stroke 1 (IQR 0-2), mean volume of DWI lesion at admission 5.7 ml (SD 12.8), mean FLAIR final infarct volume 10 ml (SD 14.9), cortical affection in 61% of infarctions. Acute DWI lesion volume on admission MRI was moderately correlated to admission/maximum IL-6 as well as maximum LBP. Extent of perfusion deficit and mismatch were moderately correlated to admission/maximum IL-6 levels. Final lesion volume on FLAIR was moderately correlated to admission IL-6 levels. Conclusion: We found IL-6 to be associated with several parameters from acute stroke MRI (acute DWI lesion, perfusion deficit, final infarct size and affection of cortex) in a cohort of patients not influenced by infections. Clinical Trial Registration: clinicaltrials.gov NCT01079728 and NCT00715533